1999
DOI: 10.1177/000348949910800717
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Diagnosis of Esophageal Bone Impaction: A Prospective Study

Abstract: A prospective study was performed on 45 patients for an assessment of the use of computed tomography (CT) in the management of a suspected esophageal fish bone or chicken bone. All patients had negative findings on laryngoscopy; therefore, pharyngeal and hypopharyngeal foreign bodies were excluded from further consideration. The patients underwent radiographic examination with plain films and a cervical CT scan without contrast material. Patients with positive findings were taken to the operating room, where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 8 publications
2
55
1
4
Order By: Relevance
“…To date, several studies have been published on the usefulness of CT (Eliashar et al 1999;Lue et al 2000) for cases in which an impacted fish bone in the pharynx-esophagus is suspected. In our patient, we identified the foreign object by using intraoperative ultrasonography, as well as preoperative assessment, avoiding the risk of accidental bleeding or tissue damage that may be caused by blind exploration.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have been published on the usefulness of CT (Eliashar et al 1999;Lue et al 2000) for cases in which an impacted fish bone in the pharynx-esophagus is suspected. In our patient, we identified the foreign object by using intraoperative ultrasonography, as well as preoperative assessment, avoiding the risk of accidental bleeding or tissue damage that may be caused by blind exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrograffin may be helpful in localizing a suspected perforation but causes severe pneumonitis if aspirated due to its hypertonicity. CT can occasionally detect objects that are missed by other modalities [32,33] and is useful in detecting complications [34,35]. It is imperative to remember that failure to demonstrate a foreign body radiographically does not preclude its presence.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…The percentage of false positive results in this study was 22%. (7,8,9) Studies have found that plain film is false negative in 30 to 55% of cases and false positive in 24% cases. 5(8%) cases showed indirect evidence of foreign bodies in digital X-ray in this study.…”
Section: Discussionmentioning
confidence: 99%